PENGARUH HAMBATAN ALIRAN UDARA PADA KONDENSER TERHADAP PERFORMANSI AC SPLIT 1 PK - Triaji Pangripto Pramudantoro Pramudantoro (Retii, 2021)
ABSTRACT Poor maintenance will decrease the performance of the split Air Conditioning unit, some cases that are often encountered include: the fins on the outdoor unit are dirty, fragile or even fold. Disruption of air flow in the outdoor unit will then have an impact on the performance of the split A/C unit, especially on cooling rate, working pressure, coefficient of performance and consumption of electrical energy. The purpose of this study was to determine the correlation/impact of airflow resistance in the outdoor unit on A/C unit performance and the magnitude of changes/increases in electrical energy consumption. The method used is by comparing the normal performance without being disturbed by the air flow in the outdoor unit compared to the engine with the outdoor unit airflow experiencing obstacles. Starting with a given resistance successively equal to 1/6, 1/8 and 1/4 of the surface area of ​​the condenser. The results obtained in the form of an increase in discharge temperature, suction temperature, condenser temperature, evaporator temperature and electric current. On the other hand, there was a decrease in the refrigeration effect by 6.25%, a decrease in the COP value from 4.63 to 3.7 and an increase in electrical power consumption by 9.3%. Keywords: condenser air flow, split AC.